Kidney utilization in the Netherlands – do we optimally use our donor organs?. Issue 3 (1st November 2022) - Schutter, Rianne; Vrijlandt, Willemijn A L; Weima, Gelske M; Pol, Robert A; Sanders, Jan-Stephan F; Crop, Meindert J; Leuvenink, Henri G D; Moers, Cyril
ABSTRACT: Background: To ensure optimal utilization of deceased donor kidneys, it is important to understand the precise reasons why kidneys are discarded. In this study we aimed to obtain a comprehensive overview of kidney utilization and discard during the entire donation process in the Netherlands. Methods: In this retrospective cohort study we analysed kidney utilization of 3856 kidneys in the Netherlands between 1 January 2015 and 31 December 2020. For every kidney that was not transplanted, we determined the moment of and reason for discard through a unique case-by-case assessment. Results: Kidney discard according to the traditional definition (procured but not transplanted) was 7.8%. However, when kidneys that seemed medically suitable at the beginning of the donation process were also included, many more potential donor kidneys were lost and the total non-utilization was 24.4%. Subjectively presumed impaired organ quality was responsible for 34.2% of all discarded kidneys. Two-thirds of kidneys discarded due to acute kidney injury (AKI) had only AKI stage 1 or 2. Conclusion: The classical definition of organ discard underestimates the non-utilization of deceased donor kidneys. Strategies to improve kidney utilization could be a revision of the maximum allowed agonal time in donation after circulatory death, careful consideration in reporting and accepting kidneys from donors with AKI and a prospectively filled registry of detailed organ discard reasons, including the 'silent' non-utilization before procurement. Graphical Abstract: